PELAKSANAAN TUGAS KERAPATAN ADAT NAGARI (KAN) TERHADAP PENYELENGGARAAN PEMERINTAHAN NAGARI PANDAI SIKEK KECAMATAN X KOTO KABUPATEN TANAH DATAR - Kurnia Kharima Asyifa Asyifa; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Kerapatan Adat Nagari or known as KAN does not only play a role in carrying out customs, arts and culture, but is also involved in and directly related to the administration of the nagari administration. The existence of a strong KAN in the nagari influences the running of the nagari government. The implementation of the tasks of KAN Pandai Sikek in administering the nagari government can be seen in the formation of nagari regulations related to adat and KAN is also present in the nagari deliberations. This study used a qualitative approach with a descriptive research type. The theory used in viewing the existence of KAN is institutional theory with the perspective of institutional logic according to Zilbert. Meanwhile, the theory used in looking at the power relationship between KAN and the Nagari Pandai Sikek government is the theory of power sharing put forward by Montesquieu. The results of the study, namely the existence of KAN based on the perspective put forward by Zilbert, show that the institutional integration and management structure of KAN was chosen based on consensus. The implementation of the duties and functions of KAN is regulated in West Sumatra Regional Regulation Number 2 of 2007 and Tanah Datar Regional Regulation Number 4 of 2008. Meanwhile, in Nagari Pandai Sikek, the duties and functions of KAN are regulated in Nagari Pandai Sikek Regulation Number 2 of 2013. The existence of KAN in Nagari is not regardless of changes in the government system. The relationship between KAN and the nagari government is known as Tali Tigo Sapilin, Tungku Tigo Sarangan, which means that KAN and the nagari government jointly resolve problems through deliberations. In carrying out its duties, KAN Pandai Sikek has not fulfilled the expectations of the Tanah Datar Regional Regulation No. 4 of 2008 because it only participates in making nagari regulations in customary affairs, but KAN Pandai Sikek has great influence in Nagari as evidenced by the existence of nagari regulations related to customary governance in the nagari. Keywords: Existence, KAN Task Implementation, Nagari Government.